Outcome of nucleos(t)ide analog intervention in patients with preventive or on‐demand therapy for hepatitis B virus reactivation. Issue 6 (5th October 2020) - Tamori, Akihiro; Kimura, Kiminori; Kioka, Kiyohide; Enomoto, Hirayuki; Odagiri, Naoshi; Kozuka, Ritsuzo; Uchida‐Kobayashi, Sawako; Enomoto, Masaru; Kawada, Norifumi; Mizokami, Masashi
Abstract: Preventive or on‐demand nucleos(t)ide analog (NA) therapy can prevent severe hepatitis related to hepatitis B virus reactivation (HBV‐R). However, it is unclear if NA can be safely stopped in such patients after cytotoxic therapies or during immunosuppressive therapies. We retrospectively evaluated 133 patients who initiated NA therapy between 2007 and 2018. A total of 103 patients were positive for HBV surface antigen (HBsAg) at baseline, and NA therapy was started before cytotoxic or immunosuppressive therapy (preventive group). Thirty patients with resolved HBV infection were treated with NA therapy after HBV reactivation (on‐demand group). Virological relapse was defined as a serum HBV DNA level >20 IU/ml. NA therapy was stopped in 12 (12%) patients (preventive group), and in 16 (53%) patients (on‐demand group). After the cessation of NA therapy, the cumulative rates of relapse were 36% and 39% at 12 and 24 months, respectively. High levels of HBsAg both at baseline and at the cessation of NA therapy were related to the occurrence of relapse. Relapse did not occur in patients with HBsAg levels <20 IU/ml (preventive group). HBV relapse occurred in five (33%) patients in the on‐demand group. Relapse occurred only in anti‐HBs‐negative patients at the cessation of NA therapy. There were no cases of hepatitis flare after the cessation of NA therapy. HBsAg predicted HBV relapse after the cessation of NA therapy in HBsAg‐positive patients. Anti‐HBs could be a predictive marker for NA therapy cessation in patients with resolved HBV. Highlights: There were few reports about the long‐term outcome of HBV reactivated patients treated with nucleos(t)ide analogue (NA). In particular, the end of prophylactic NA therapy was not evaluated. HBsAg <20 IU/mL predicted HBV no relapse after NA cessation in patients with preventing therapy. Patients with on‐demand therapy, anti‐HBs could be a predictive marker for NA cessation.